Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, fall 1997 - Proescholdt, Market al (1997)
Fall report of birds and locations contributed by Mark Proescholdt and other observers. Also includes a brief note from Proescholdt to Thomas H. Kent regarding the fall birding season and the upcoming fall report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed